A case-control study and meta-analysis confirm glucokinase regulatory gene rs780094 is a risk factor for gestational diabetes mellitus - Jamalpour, Sajad; Zain, Shamsul Mohd; Mosavat, Maryam; Mohamed, Zahurin; Omar, Siti Zawiah (Elsevier, 2018)
Background: Although the influence of a common variant in the glucokinase regulatory gene (GCKR rs780094) in type 2 diabetes mellitus has been well documented, less data however, is available of its role in gestational diabetes mellitus (GDM). We carried out a case control study to assess the association between GCKR rs780094 and GDM in the Asian, and also a meta-analysis to further assess the strength of the association. Methods: Demographic, clinical and genotype data were determined for 1122 women (267 cases and 855 controls) recruited from the University of Malaya Medical Centre in the Klang Valley, Kuala Lumpur. Relevant articles were identified from Pubmed, Embase, MEDLINE, and Web of Science. Extraction of data was carried out and summary estimates of the association between rs780094 and GDM were examined. Results: The frequency of risk allele C was significantly higher in the cases than controls (OR 1.34, 95% CI 1.09–1.66, P = 0.006). The C allele was also associated with increased level of random 2-hour fasting plasma glucose and pregravid body mass index. Meta-analysis further confirmed the association of the GCKR rs780094 with GDM (OR 1.32, 95% CI 1.14–1.52, P = 0.0001). Conclusion: This study strongly suggests that GCKR rs780094-C is associated with increased risk of GDM.